Spontaneous abortions in hospital staff engaged in sterilising instruments with chemical agents. Issue 6353 (20th November 1982) - Hemminki, K; Mutanen, P; Saloniemi, I; Niemi, M L; Vainio, H
Abstract : Spontaneous abortions in hospital sterilising staff were analysed using data from a postal questionnaire and a hospital discharge register. The study included all the sterilising staff employed in Finnish hospitals in 1980; the controls were nursing auxiliaries. Data from the questionnaire showed that the frequency of spontaneous abortions was 11.3% for the sterilising staff and 10.6% for the nursing auxiliaries. When the staff were concerned in sterilising procedures during their pregnancy the frequency was 16.7% compared with 5.6% for the non-exposed pregnancies. Adjustment for age, parity, decade of pregnancy, smoking habits, and intake of coffee and alcohol did not affect the differences. The increased frequency of spontaneous abortion correlated with exposure to ethylene oxide but not with exposure to glutaraldehyde or to formaldehyde. Analysis of spontaneous abortions from the hospital discharge register confirmed the findings. Thus the results from the two independent analyses suggest that exposure to ethylene oxide in hospitals may carry a risk of spontaneous abortion among sterilising staff.